2016
DOI: 10.1371/journal.pone.0152570
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Fucoidan from Fucus vesiculosus Protected against ConA-Induced Acute Liver Injury by Inhibiting Both Intrinsic and Extrinsic Apoptosis

Abstract: This study aimed to explore the effects of fucoidan from Fucus vesiculosus on concanavalin A (ConA)-induced acute liver injury in mice. Pretreatment with fucoidan protected liver function indicated by ALT, AST and histopathological changes by suppressing inflammatory cytokines, such as tumor necrosis factor alpha (TNF-α) and interferon gamma (IFN-γ). In addition, intrinsic and extrinsic apoptosis mediated by Bax, Bid, Bcl-2, Bcl-xL and Caspase 3, 8, and 9 were inhibited by fucoidan and the action was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 52 publications
(44 reference statements)
1
30
1
Order By: Relevance
“…In our study, the grading of leukopenia, anemia, and thrombocytopenia was similar in both groups. Fucoidan has been reported to protect against liver injury and liver fibrosis in mice [38,39]. However, we did not observe this benefit with regard to chemotarget agents.…”
Section: Discussioncontrasting
confidence: 94%
“…In our study, the grading of leukopenia, anemia, and thrombocytopenia was similar in both groups. Fucoidan has been reported to protect against liver injury and liver fibrosis in mice [38,39]. However, we did not observe this benefit with regard to chemotarget agents.…”
Section: Discussioncontrasting
confidence: 94%
“…Further, we plan to do more studies on the treatment of quercetin for liver diseases, such as hepatitis 54 , 55 , inflammation associated hepatic diseases 56 , and hepatocellular carcinoma 57 – 59 . And we hope that quercetin can delay the progression of liver diseases, and cure them.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that oral fucoidan can reduce liver fibrosis and has anti-inflammatory effects in patients with non-alcoholic hepatitis (NAFLD) [17,19,21,22]. In an animal experiment, ALT and AST in the serum increased after ConA-induced liver inflammation in mice, and ALT and AST decreased in a dose-dependent manner after adding different concentrations of fucoidan [27]. Animal studies have also demonstrated that fucoidan reduces the titers of mouse liver virus B and HBsAg [28].…”
Section: Discussionmentioning
confidence: 97%